IMPLEMENTATION OF INTELLECTUAL PROPERTY LAW AWARENESS AND CYBERSECURITY TECHNOLOGY AGAINST DIGITAL COPYRIGHT VIOLATIONS IN INDONESIA DURING THE 2024 ELECTIONS - Yoan Shevila Kristiyenda; Tasya Safiranita Ramli (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
The rapid growth of internet users in Indonesia has driven digitalization across various aspects of life, including the 2024 General Election. However, this increase in digital activity also raises serious challenges related to the protection of intellectual property rights and digital rights, such as copyright infringement, the spread of hoax information, and cyberattacks that potentially threaten the integrity of democracy. Based on this background, this study examines how awareness of Intellectual Property Rights and cybersecurity technology impacts digital copyright infringement and digital rights violations in the 2024 General Election. This research uses a normative-empirical legal method, combining field and literature studies, to analyze the effectiveness of regulations and public awareness of Intellectual Property Rights. The analysis refers to Soerjono Soekanto’s Theory of Legal Awareness, which outlines four progressive indicators: legal knowledge, legal understanding, legal attitude, and legal behavior. These indicators serve as a framework to assess how public knowledge, understanding, attitudes, and behavior toward intellectual property and cybersecurity influence the level of digital rights violations in Indonesia during the 2024 General Elections. The results show that weak public understanding of intellectual property rights contributed to widespread copyright infringement, while hoaxes and weak cybersecurity threatened the integrity of the election. Thus, the spread of hoaxes on social media and weak cybersecurity highlighted the need for collaboration among the government, the public, and the media. Strengthening regulations, increasing legal awareness, and adherence to cybersecurity standards are key to maintaining the integrity of information and electronic systems during General Elections.